Analyzing the Subordinate Resurrection (Gathering) from the Perspective of Ṣadr al-Mutiʾallihīn and Facing Difficulties of Returning Toward God - Sayyid Muhammad Mousavi Baygi; Muhammad Taqi Rajaei; Mustafa Faqih Esfandiari (آموزه‌‌های فلسفه اسلامي)
Mullā Ṣadrā has explained the resurrection (Arabic: معاد) and gathering (Arabic: حشر) based on his principles. The consequential (subordinate) and independent resurrection is one of the important and useful points in his explanation but which less attention has been paid to it. Ṣadr al-Mutiʾallihīn (Arabic: صدر المتألّهِین) himself did not mention the term “subordinate” and “independent”, but Muḥaqqiq Sabziwārī mentioned it in his commentary on al-Asfār al-arbaʿa (Arabic: الأسفار الأربعة). Ṣadr al-Mutiʾallihīn believes that gathering (Arabic: حشر) means to raise the level of existence and access to the upper world, which is possible with the essential progressive motion. All creatures in the world of nature have become progressed to the substantial motion and their order of existence is increased. This is their gathering they have reached. It is possible to accept a subordinate gathering for the creatures in addition to this kind of gathering which is independent. The effect is the same as the relation to the cause and exists in the order of the cause briefly and its cause is also related to its own cause and is present with it. The presence of the effect in the presence of the cause of the cause is called a secondary (subordinate) resurrection (gathering). We tried, in this article, to explain the issue of consequential and independence Hashr (resurrection or gathering) in such a way to solve the problems and dilemmas facing the philosophical explanation of Hashr and return toward God (Arabic: رجوع إلی اللّٰه). All levels of existence, from the inferior level to the superior level, refer to God Almighty based on this.